Big data, little data, no data : scholarship in the networked world - Borgman, Christine L., 1951- (The MIT Press, 2015)
An examination of the uses of data within a changing knowledge infrastructure, offering analysis and case studies from the sciences, social sciences, and humanities.
Keywords: Communication in learning and scholarship -- Technological innovations.; Research -- Methodology.; Research -- Data processing.; Information technology.; Information storage and retrieval systems.; Cyberinfrastructure.; elektronické knihy; electronic books